The Community Partnership Program BUMDES Catu Graha Mandiri in Gumbrih Tourism Village, Pekutatan, Jembrana, Bali - I Wayan Ruspendi Junaedi; Gerson Feoh; I Gusti Bagus Rai Utama (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2021)
The partnership program between Dhyana Pura University and Catu Graha Mandiri BUMDES was applied by socialization activity, management training, mentoring, and evaluation. The program used a business management indicator that aims to improve the knowledge and skills of the Catu Graha Mandiri BUMDES community business group members. The partnership programs were measured by Pre-Test and Post-Test Method so that the effectiveness and output of the program can be measured accurately. The program offered the solution in terms of providing assistance and training on the use of appropriate technology in increasing the quantity and quality of production of BUMDES Catu Graha Mandiri Gumbrih Village, as well as making financial reports, providing assistance and training on management, education on ethics and consumer behavior, and training product marketing using social media. The results of this partnership program have been able to improve the services of BUMDES Catu Graha Mandiri Gumbrih to consumers and be able to make financial reports accurately. The sales turnover of partners BUMDES has also increased and developed so that job opportunities are open to the community as well as the addition of new entrepreneurs in Gumbrih Village. The increase in human resources in the application of professional management has also increased, an increase in business production has also occurred, marketing has also increased and financial reports can also be done regularly, and promotions on social media have increased so that the sales turnover of BUMDES partners Catu Graha Mandiri Desa Gumbrih more increasing. Keywords: digital marketing; finance management; technology; tourism village